A general and concise stereodivergent chiral pool approach toward trans-(4S, 5R)- and cis-(4R, 5R)-5-alkyl-4-methyl-γ-butyrolactones: Syntheses of (+)-trans- and (+)-cis-whisky and cognac lactones from d-(+)-mannitol. (December 2021) - Manna, Avrajit; Chakraborty, Ipsita; Chatterjee, Sandip; Bhaumik, Tanurima
Abstract: A straightforward synthesis of (+)- trans -(4 S, 5 R )- and (+)- cis -(4 R, 5 R )-whisky lactones starting from d -(+)-mannitol has been reported here in fewer number of efficient steps compared to existing literature processes involving d -mannitol as the chiral pool starting material. Chiron approach directly translated chirality of d -mannitol to one of the two chiral centers in these target molecules. Toward this end, stereoisomerically pure trans- and cis- iodomethyl-γ-lactones were formed in the penultimate step. These two acted as versatile advanced common intermediates as they were also converted to the (+)- trans -(4 S, 5 R )- and (+)- cis -(4 R, 5 R )-cognac lactones, respectively. To the best of our knowledge, till date no synthesis of cognac lactones starting from d -mannitol has been reported. All these lactones are identified as the key aroma components of aged alcoholic beverages. Graphical abstract: Image 1 Highlights: A convenient general and straightforward synthetic route has been reported. Chiron approach conveyed stereochemistry from d -mannitol to the C-5 chiral center. Stereoselective hydrogenation led to stereodivergence at the C-4 chiral center. Fewer steps to whisky lactones from d -mannitol compared to literature syntheses. First report of syntheses of cognac lactones starting from d -(+)-mannitol.